Factors influencing work stress - Nur Fatin Izzati, Mohamad Said (2020)
The research aim is to determine factors influencing work stress among the employees in one of the Islamic Financial Institutions in the northern region of Malaysia. The research also intends to determine whether there were any statistically significant relationships between work stress with the independent variables (work overload, physical work environment, co-worker relationship and social support). A total of 120 employees involved in the research from 11 branches of the institutions in Kedah state. The research used a quantitative method and cross-sectional research design was applied. The data and information were collected through online questionnaires and the data obtained were analyzed using Statistical Package for Social Sciences version 26.0. Descriptive analysis was conducted to analyze demographic data (gender, age, marital status, education level and working experience). Correlation and regression analysis were used to analyze the relationship between work stress, with work overload, physical work environment, co-worker relationship and social support. The findings of the research showed that work overload, physical work environment, co-worker relationship, and social support have significantly influence work stress. There were positive significant relationships between work stress with workload, physical work environment, co-worker relationship and social support.